HUBUNGAN BERAT BADAN LAHIR RENDAH (BBLR) DENGAN KEJADIAN STUNTING PADA ANAK USIA 2-5 TAHUN DI WILAYAH KERJA PUSKESMAS SLEMAN - Melinda Umagapi,; Fitnaningsih Endang Cahyawati,; Ellyda Rizky Wijhati3, (Journal of Innovation Research and Knowledge, 2025)
Background: Stunting is a significant health challenge in Indonesia and has become a key target for nutritional improvement in the country. According to data from the DIY Health Office, the prevalence of stunting was 16.4% in 2022. Sleman Regency ranked third, with a prevalence of 15.0%, while the prevalence of stunting in the Puskesmas (community Health Center) Sleman service area was 3.53% in 2023. Globally, 15.5% of births, or approximately 20 million children annually, experience low birth weight (LBW). In 2023, 8.79% of LBW cases were recorded in Puskesmas Sleman. Objective: This study aims to investigate the relationship between low birth weight (LBW) and the incidence of stunting in children aged 2–5 years in the Puskesmas Sleman service area. Method: This study employed quantitative design with survey method and case-control approach. Statistical analysis was conducted using the Chi-square test. The study population consisted of 1,538 under-five children. The sampling technique used total sampling for the case group and random sampling for the control group. The total sample size, based on the collected data, was 140 participants, comprising 70 cases and 70 controls. Data collection was performed using records from Posyandu (Integrated Health Post) registration reports, entered into a structured data collection format, and guided by a checklist. Results: Among the respondents, 24 (17.1%) experienced LBW, while 116 (82.9%) did not. The number of respondents with stunting was 70 (50.0%), and those without stunting also totaled 70 (50.0%). The Chi-square test showed a p-value of 0.000, and the odds ratio (OR) was 9.571. Since the p-value is less than 0.05, a significant relationship exists between LBW and the incidence of stunting. Children with LBW were found to have a 9.571 times higher risk of stunting compared to those without LBW. It is recommended to optimize socialization programs for pregnant women to prevent LBW and stunting. Ensuring every family member maintains good nutritional status, especially children, can help improve the nutritional status of children aged 2–5 years and contribute to better outcomes as they grow older.